A Study on Relationship between Customers Demand and Customers Perception on Transition of SOCSO as Shariah Compliance Organization - Mohd Shafiz Bin Saharan; Masilah Mohamad; Hanani Hussin; Mohd Fazil Jamaludin; Khairul Azfar Adzahar (International Journal of Supply Chain Management, 2018)
This study attempts to examine customers demand and its relationship on customers perceptions on the transition of SOCSO (Social Security Organization of Malaysia) as Shariah compliance organization. The objective of this paper is to determine whether customers demand has a significant relationship with customers perception. Data were collected using questionnaire survey method and a total of 132 questionnaires distributed to SOCSO contributors at Alor Setar, Kedah. Data were analyzed by the use of descriptive analysis and correlation analysis that presented in a table. The result shows a significant positive relationship between the independent variable and dependent variable. Therefore, it is important to look into extensive effort on the Islamization of SOCSO so that the demand from the Muslims employees to have Islamic social security program can be achieved.